Nephrological complications in patients after COVID-19 infection - Marciniak, Agnieszka; Nemeczek, Sylwia; Walczak, Klaudia; Walczak, Patrycja; Merkisz, Konrad; Grzybowski, Jakub; Grzywna, Natalia; Jaskuła, Karolina; Orłowski, Władysław (Quality in Sport, 2023)
In this review, we looked for correlations and health consequences between COVID-19 infection and kidney health. Although the main symptoms of COVID-19 are respiratory failure and hypoxemia, kidney involvement is also common. In an attempt to decipher how COVID-19 infection affects the kidneys, this review focuses on the pathophysiological and clinical links between COVID-19 infection and the kidneys. The aim of this work was to find long-term health consequences in patients who were discharged from the hospital and to investigate risk factors. COVID-19-related kidney disease is reported not only in infected patients with chronic kidney disease, but also in people with no previous history of kidney disease. The disease caused by the coronavirus (COVID-19) is a threat to public health. Chronic kidney disease (CKD) has been shown to be a risk factor for side effects. Although initial reports from China showed a low incidence (5%-10%) of acute kidney injury (AKI), subsequent articles documented a much higher incidence of AKI in hospitalized COVID-19 patients. Overall, renal biopsies showed a variety of histopathology, including acute glomerulonephritis and acute tubular injury. The pathophysiology of COVID-19-associated AKI is believed to include local and systemic inflammatory and immunological reactions, endothelial damage, and activation of coagulation pathways and the renin-angiotensin system. Histopathology results revealed both similarities and differences between AKI in COVID-19 patients and AKI patients in non-COVID-19 sepsis. Acute tubular injury is common, although it is often mild despite greatly reduced kidney function. Systemic haemodynamic instability most likely contributes to renal tubular damage. Despite the description of COVID-19 as a cytokine storm syndrome, circulating cytokine levels are often lower in patients with COVID-19 than in patients with acute respiratory distress syndrome from causes other than COVID-19. Also, an impaired response to type I interferon has been detected in patients with severe COVID-19. In the light of these observations, the potential pathophysiological mechanisms of COVID-19-associated AKI may provide knowledge to construct therapeutic strategies.